Regional agreements and the World Trade Organization (WTO) - Vilar Rubiano, Fabián Enrique (DIXI, 2019)
Objective: With the accelerated increase in economic integration today, it is vitally important to study Regional Trade Agreements (RTAs).Methodology: This article constitutes an analysis of the most relevant aspects of RTAs within the framework of the Multilateral Trading System.Results: The increase in RTAs becomes a challenge for the validity of the Multilateral Trade System, which must resort to achieving a necessary consensus to avoid its disappearance.
Keywords: Regional Trade Agreements; economic integration; World Trade Organization; regionalism; transparency